DESIGNING THE COVER OF THE FANTASY NOVEL ‘ALPHERATZ CHRONICLE: GUIDE TO AN UPRISING’ TO FIT THE MARKET - Rahmadiva, Atita Sashita; Sutanto, Shienny (Universitas Ciputra, 2023)
The illustrations in the book or the cover in the book have the intention to explain the contents of the book. Popular fantasy novels like The Little Prince by Antoine de Saint-Exupéry, have illustrations from book covers to book contents. The novel 'Alpheratz Chronicle: Guide to an Uprising' is one of the novels inspired by popular fantasy novels. But 'Alpheratz Chronicle: Guide to an Uprising' does not yet have a visual for the book to be marketable. Therefore, in order for the original novel 'Alpheratz Chronicle: Guide to an Uprising' to be more acceptable and attractive in the eyes of readers, a visualization design for the cover and contents of the novel 'Alpheratz Chronicle: Guide to an Uprising' was made using art style that determined by research over the topic. This study uses questionnaires and interviews with expert users who are proficient in this field and extreme users who frequently consume the product. The results of the questionnaires and interviews will determine what artstyle makes the original fantasy novel more interesting and whether the resulting prototype from the design meets the criteria to be a marketable book or not. Therefore, it is hoped that the results of the visualization design of the original novel 'Alpheratz Chronicle: Guide to an Uprising' are expected.